The Predictability of Future Aggregate Earnings Growth and the Relation between Aggregate Analyst Recommendation Changes and Future Returns - Billings, Bruce K.; Keskek, Sami; Pierce, Spencer (The Accounting Review, 2021)
ABSTRACT We extend prior research examining the relation between aggregate recommendation changes and future returns by documenting that this relation varies over time as a function of the predictability of future earnings growth. When industry-level earnings growth is more predictable, we find that recommendation changes relate negatively to future returns. Our evidence suggests that this negative relation results from analysts revising recommendations upward for higher expected earnings growth but failing to also adjust downward for a related decrease in expected returns arising from a decrease in investor risk aversion. In contrast, when industry-level earnings growth is less predictable, we find that recommendation changes relate positively to future returns. However, this positive relation results from analysts and investors similarly underestimating earnings growth persistence. Overall, the evidence fails to support the claim that analysts' recommendation changes incorporate aggregate information in a manner that adds value to investors by predicting future returns. JEL Classifications: A10; E10; E44; E52; G11; G14; M40; M41.